Gender Equality and ESI in the English Language Classroom: a Teaching Experience with Children - Maití, María Pía (2018)
Gender equality is not a topic we could easily find in EFL textbooks, and it might seem a complex issue to discuss with children’s groups. However, teaching from a gender perspective is not only a highly enriching experience both for students and teachers alike, but also our ethical and legal responsibility as educators. At the international level, Gender Equality is the fifth goal of the United Nations Sustainable Development Agenda for 2030. Sustainable Development Goal number 5 aims at ending all forms of discrimination and violence against women and girls and ensuring equal opportunities for everyone in order to achieve a peaceful, prosperous and sustainable world. At a national level, the National Program on Comprehensive Sex Education, known as ESI, started in 2006 and one of its objectives is to guarantee gender equality among men and women. Having the international and national framework into account, this paper presents a project developed with children at Escuela de Lenguas, FAHCE-UNLP, which aimed at debunking gender stereotypes in traditional fairy tales and promoting gender equality.